Same author, same stories, different unity: a close comparative reading of a selection of stories from Raymond Carver’s What we talk about when we talk about love and beginners - Carter, Kaitlyn (My University, 2023)
This essay provides a close comparative reading of three stories from Raymond Carver’s short story cycles Beginners and What We Talk About When We Talk About Love. A working definition of short story cycles is developed and referenced in the evaluations of these stories—this definition utilizes literary scholar Gerald Lynch’s work on the sub-genre. The close comparative analyses of “Why Don’t You Dance?”, “One More Thing”, and “Gazebo” reveal that both collections meet the criteria of short story cycles, however Beginners has a stronger unity that achieved through its shared themes. This supports the argument that Carver’s editor, Gordon Lish, exchanged Carver’s unity of theme in Beginners for a weaker unity of style in What We Talk About.
Presented February 2-3, 2024 at the English Student Conference 2024 held at MacEwan University in Edmonton, Alberta.
Keywords: short story cycles; Raymond Carver